2008
DOI: 10.1007/s11605-008-0513-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Nonrandomized Comparison Between Pylorus-Preserving and Subtotal Stomach-Preserving Pancreaticoduodenectomy from the Perspectives of DGE Occurrence and Postoperative Digestive Functions

Abstract: Despite the bias of the operative factors, the incidence of DGE and postoperative dietary intake after SSPPD was comparable with PPPD, and therefore, pylorus preservation seemed to have no impact on postoperative dietary intake or DGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…In some historical studies, the incidence of DGE was lower in the CW or SSPPD group than in the PPPD group. 34,35 A possible reason for a higher incidence of DGE in the PPPD group is that duodenojejunostomy is narrower than gastrojejunostomy, while the remnant stomach is larger in the PPPD group than in the CW group, which might disturb the passage of the food. However, three prospective randomized trials and a meta-analysis have negated the advantage of the CW over PPPD groups.…”
Section: Discussionmentioning
confidence: 99%
“…In some historical studies, the incidence of DGE was lower in the CW or SSPPD group than in the PPPD group. 34,35 A possible reason for a higher incidence of DGE in the PPPD group is that duodenojejunostomy is narrower than gastrojejunostomy, while the remnant stomach is larger in the PPPD group than in the CW group, which might disturb the passage of the food. However, three prospective randomized trials and a meta-analysis have negated the advantage of the CW over PPPD groups.…”
Section: Discussionmentioning
confidence: 99%
“…Akizuki et al [20] reported that the incidence of DGE was similar in PPPD and SSPPD, and lymph node dissection did not affect the incidence of DGE. The divergence of results may be caused by difference of reconstruction method.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 94%
“…In most previous studies about DGE, a comparison was made of those who received classic PD versus PPPD. There are few studies on comparison of DGE between PPPD and SSPPD [19,20], and the benefit of SSPPD remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this was impossible to discern in the included trials. This global meta-analysis included all types of PD techniques as several articles proved that pylorus preservation did not influence DGE incidence [6,43,[53][54][55][56][57][58][59][60][61] . Interventions consisted of cPD (2 studies including cPD and ppPD), ppPD (3 studies), and sspPD (1 study), which can bring some heterogeneity.…”
Section: Quality Of the Evidence Strengths And Potential Biases In mentioning
confidence: 99%
“…DGE after PD is one of the most frequently described specific complications [4,5] with reported incidences between 20 and 40% [6][7][8] . Its occurrence often represents a troublesome postoperative complication for patients and surgeons [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%